Interrelationships between the personal variables and entrepreneurial potentials of senior students of UUM - Barcelona, Aurora C.; Valida, Abelardo C. (Universiti Utara Malaysia, 1992)
To help understand better how UUM's avowed mission of developing qualified human resources in the field of management and entrepreneurial development can best be realized, in consonance with vision 2020, this descriptive study attempted to establish the profile and entrepreneurial potentials of eight-hundred randomly selected, senior students of UUM, who were enrolled during the school year 1991-1992 and analyze the interrelationships between those. It was hypothesized they there are no significant relationships between the students personal variables and their mean entrepreneurial character trait ratings. A set of Questionnaire (translated to Bahasa Malaysia) made up of two parts, namely: Respondents Profile and Character Traits of Potential Entrepreneurs was used. The latter part of the instrument have been employed in, at least, four other prior research studies. Our findings show that the subjects exhibited "medium" entrepreneurial character trait ratings, except for knowledgeable, which was reported to be "low". A good number of significant relationships identified can help guide educational planners and policy makers in attuning existing study programs so as to provide the best educational strategy and services at UUM. The study is anchored upon a firm belief that entrepreneurial development will ultimately be the major means towards achieving quality and productivity - the epitome upon which Vision 2020 rests - and, thus, significantly minimize the problem of social-economic inequality.